Determinants and consequences of applying value-based performance measures: the German evidence. (16th February 2010) - Ernstberger, Jurgen; Egger, Florian; Giebelstein, Matthias
This paper examines the determinants of applying value-based performance measures like economic value added (EVA) and the impact of applying these measures on firms' returns. Our research design exploits a unique situation in Germany, where a regulatory change requires firms to describe their performance measurement system in their annual report since 2006. Analysing these disclosures, we find that firm size and firm age have a positive impact on the propensity of applying value-based performance measures. In a second analysis, we are not able to document a positive influence of the application of value-based performance measures on firms' performance. However, we find a significant positive association with firm valuation when controlling for self-selection. The paper contributes to the literature, as it is the first to comprehensively investigate the determinants and consequences of applying value-based performance measures.